LOCKED DOWN IN THE RAINBOW NATION: ALLEVIATING THE LONELINESS OF SOUTH AFRICAN OLDER PERSONS - Geyer, Stephan; Chonody, Jill; Teater, Barbra (Social Work/Maatskaplike Werk, 2023)
The literature on the biopsychosocial effects of COVID-19 on older persons has originated predominately from the Global North, with a dearth of studies focusing on the loneliness of older persons in the developing world, such as South Africa. This cross-sectional study explored the loneliness of South African older persons (N = 118) before and during COVID-19 to inform gerontological social work. The survey incorporated a standardised scale of loneliness and items to assess the type and quantity of contact with others, physical health, mental health and socio-demographic variables. Bivariate and multivariate analyses explored the factors that contributed to overall loneliness, emotional loneliness and social loneliness. Results indicated a statistically significant increase in social, emotional and overall loneliness from pre- to during COVID-19. Considered from a socio-ecological resilience perspective, gerontological social work services are recommended for alleviating loneliness amongst South African older persons during a pandemic, such as COVID-19.